HIV/AIDS-related stigma in the South African construction industry: the case of ESKOM - Fredericks, Cameron (Department of Construction Economics and Management, 2015)
The South African construction industry has not responded effectively to address the high HIV-prevalence rate within its workforce. The Western Cape construction industry is the least responsive. No formal studies have examined how the construction industry's unresponsiveness to the pandemic has impacted Eskom's capital construction projects. Central to the fight against the spread of the disease is voluntary testing and counselling (VCT). AIDS-related stigma and discrimination are impediments to VCT. The aim of this study is to explore how stigmatisation and discrimination of HIV/AIDS positive persons negatively impacts site-based HIV/AIDS intervention programmes implemented at Eskom construction sites. The three main objectives are: to determine the current attitude and views Koeberg employees have towards HIV/AIDS; to determine if the stigma of HIV/AIDS prevents Koeberg employees from accessing HIV intervention programmes offered at Koeberg; and to determine the percentage of Koeberg employees utilising the HIV intervention programme at Koeberg. A self-administered questionnaire gathered data from 296 site-based employees, mostly contract construction workers, at Koeberg Nuclear Power Station, located in Cape Town. The data were analysed using Pearson's product-moment correlation, the test for differences in means, the chi- square test for independence, and multiple regression analysis. These statistical analyses were conducted to determine relationships among 'demographic' variables (age, gender, ethnicity, employment type, marital status and education level) and 'cognitive ' and 'behavioural' factors ('lifestyle risk', 'condom non-compliance', 'substance use', 'HIV/AIDS knowledge', and 'attitudinal fear of testing') - to predict HIV/AIDS-related stigma. The results indicate that: (1) age predicts lifestyle risk, condom non-compliance and alcohol consumption - younger workers i.e., under 30 years, consume more alcohol , partake to a greater extent in riskier sexual affairs , but practice safer sex than older workers; (2) gender predicts lifestyle risk and alcohol use, and directly influences attitudinal fear of being tested for HIV – younger men, particularly contract construction workers, tend to be more fearful of being tested for HIV, lead riskier sexual lifestyles, and consume greater amounts of alcohol; (3) ethnicity predicts condom non- compliance and alcohol consumption – 'White', 'Indian' and 'Coloured' men are less likely to use condoms and consume more alcohol than 'Black' African men; and (4) HIV/AIDS knowledge and attitudinal fear of testing predicts stigmatised views toward HIV/AIDS - those with lower levels of education and possessing poor knowledge about HIV/AIDS, coupled with high attitudinal fear of testing, hold highly stigmatised views towards HIV/AIDS persons. 'Coloured' employees living with HIV have higher levels of felt-stigma and enacted stigma than 'Black' African employees living with HIV. The Koeberg site-based HIV/AIDS intervention programme should increase its focus on communicating the benefits of being tested for HIV/AIDS, and encourage younger men, particularly contract construction workers, to undergo testing. Effort should also be focussed on reassuring employees about their confidentiality and dispel misinformation and myths associated with the disease. Finally, Koeberg senior management should pledge their support, influence and guide construction firms employed at Koeberg to utilise the Eskom HIV/AIDS intervention programme.